IMPLEMENTASI KEBIJAKAN RETRIBUSI IZIN GANGGUAN (HO) DI KECAMATAN CISARUA KABUPATEN SUMEDANG - Asep Kuswara (LPPM UNSAP & FISIP UNSAP, 2018)
This study aims to obtain a description of the implementation of the policy of levy permit levies (HO) in Sub Cisarua Sumedang District. The research method used is qualitative with descriptive approach. The research informants consist of Camat, Kasi Pelayanan Umum, Staf PNS pada Seksi Pelayanan Umum, Staf Non PNS pada Seksi Pelayanan Umum, entrepreneur (obligatory retribution), Kepala Desa Bantarmara dan Kepala Desa Cimara. Data collection techniques were conducted through literature studies and field studies consisting of interviews, observation and documentation. Data analysis is done by data reduction, data presentation, conclusion and composite. The result of this research is that implementation of policy of levy permit permit (HO) in Kecamatan Cisarua: Firstly, supported by communication factor, that is good socialization, clear division of authority, officers consistently apply rules and technical regulations in accordance with higher rules. But there are also communication factors that hinder the socialization has not touched the public awareness and the lack of commitment of the division of authority. Second, supported by the resource factor, namely: Employees are adequate, information how to implement the policy is adequate, compliance information on the regulatory staff is adequate, employees work based on letters of duty, and facilities are adequate. But there are also resource factors that hinder the information from the district level in the form of oral information, can not be used as a basis. Third, supported by disposition factors, namely: Employees support the success of policy implementation, employees are the most capable personnel to perform tasks, civil servants do not receive incentives because it is attached to the main task and function, while for non-civil servants available monthly incentives. Fourth, supported by bureaucratic structure factors, namely: Available SOP, there is distribution of the implementation of responsibility to the Section of Public Service.